Bioactive compounds and antioxidant capacity of fruit on Sechium edule - Albarracin, Graciela (2010)
Vegetables and fruits contain bioactive compounds with antioxidant activity such as phenols and flavonoids, carotenoids, ascorbate, alimentary fiber, selenium and many substances with antiatherogenics and anticarcinogenics properties. The purpose of this work is to assess some bioactive constituents and the antioxidant activity of the Sechium edule (Jacq) Swartz (Cucurbitaceae) fruit. Total phenol content was higher (p <0,001) in pulp (Sep):124.83mg/100g than seed (Ses): 86.36mg/100g. The antioxidant activity were estimated by: nitric oxide scavenging activity (NO), DPPH radicalscavenging activity (DPPH) and β-carotene bleaching method (β-carotene). The values expressed as percentage (%) corresponds to Ses and Sep respectively: NO 47.51 ± 1.9 and 55.62 ± 1.3; DPPH: 88.87 ± 1.1 and 89.13 ± 1.5 and β-carotene, 63.32 ± 1.5 and 53.15 ± 1.4. The studied samples have important radical scavenging activity and inhibited lipid peroxidation in vitro. We concluded that the present study provides infor- mation that Sechium edule can be a source of natural antioxidants.